Penerapan Model Value Clarification Technique (VCT) untuk Meningkatkan Pemahaman Siswa pada Pembelajaran IPS - Sriyanto Sriyanto; Sarkuji Waluya; Nurma Indah Oktaviani; Ning Breni Astuti; Komaru Zaman; Agung Sustiyawan (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The understanding acquired by students during the learning process significantly contributes to building a strong academic foundation and supports the development of essential life skills for the future. This research uses a qualitative approach. The informants in this study were Social Studies teachers. Data collection techniques included interviews, observations, and documentation. The results of this study are as follows: 1) The steps of the VCT model include: developing a complete instructional plan (scenario) outlined in the Lesson Plan (RPP) by clearly defining the targeted values; during the lesson opening, the teacher explains the learning objectives, content scope, methods, tools, and general overview; the teacher presents a stimulus and issues relevant to the learning material; students are asked to classify the material and problems, then analyze case by case, and determine their own stance along with arguments and reasoning—students are encouraged to relate the case to their own experiences; the teacher and students provide comments and engage in discussion to reinforce the students’ values; the teacher and students conclude the lesson together; 2) The advantages of the VCT include: helping students identify personal values; increasing self-awareness; encouraging responsible decision-making; developing social skills and empathy; being flexible and adaptable to various learning materials; 3) The disadvantages of the VCT are: it is not sufficient to build strong character alone; it tends to focus more on cognitive aspects and less on the affective domain; and it requires highly trained teachers. The conclusion of this study is that the VCT model can be applied in the learning process as an effort to enhance student understanding during the learning process at the Madrasah or school level.